2005
DOI: 10.1080/1360500114415
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, sense of coherence, purpose in life and self-transcendence in relation to perceived physical and mental health among the oldest old

Abstract: Different concepts have been presented which denote driving forces and strengths that contribute to a person's ability to meet and handle adversities, and keep or regain health. The aim of this study, which is a part of The Umeå 85+ study, was to describe resilience, sense of coherence, purpose in life and self-transcendence in relation to perceived physical and mental health in a sample of the oldest old. The study sample consisted of 125 participants 85 years of age or older, who ranked themselves on the Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
339
8
34

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(425 citation statements)
references
References 59 publications
30
339
8
34
Order By: Relevance
“…Alpha coefficients between 0.72 and 0.94 have been reported for the English version (Wagnild, 2009) and between 0.83 and 0.90 for the Swedish version (Nygren et al, 2004;2005). In the present study Cronbach's alpha was 0.86.…”
Section: Instruments For Validationsupporting
confidence: 51%
See 2 more Smart Citations
“…Alpha coefficients between 0.72 and 0.94 have been reported for the English version (Wagnild, 2009) and between 0.83 and 0.90 for the Swedish version (Nygren et al, 2004;2005). In the present study Cronbach's alpha was 0.86.…”
Section: Instruments For Validationsupporting
confidence: 51%
“…In a previous study we found statistically significant correlations between scores on the Resilience Scale (RS) (Wagnild and Young, 1993), the Sense of Coherence Scale (SOC) (Antonovsky, 1987), the Purpose in Life Scale (PIL) (Crumbaugh and Maholick, 1964), and the Self-Transcendence Scale (STS) (Reed, 1991) among people aged 85 years and over (Nygren et al, 2005). We concluded that these correlations indicate some common dimension of inner strength.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are in line with research with populations with other health conditions such as human immunodeficiency virus or Alzheimer disease or healthy populations. [120][121][122][123][124][125][126][127][128][129] Spirituality can be an important component in psychotherapy. [130][131][132] Beneficial effects of meaning making interventions on SE, optimism and self-esteem are reported.…”
Section: Psychological Resources In Sci C Peter Et Almentioning
confidence: 99%
“…A handful of studies have used these instruments to assess resilience in older people (Hardy et al, 2002;Nygren et al, 2005;Wagnild, 2003). Hardy et al (2004) developed a 6-item scale that assessed resilience in response to a specific life event identified by the respondent.…”
Section: Introductionmentioning
confidence: 99%